The The Development of a Vocabulary Module Using Flip PDF Corporate Software at Secondary School - Siti Feliscka Azelia Putri; Siminto, Siminto; Qamariah, Zaitun (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
ABSTRACT The research aims to contribute to teaching and learning activities in English vocabulary by developing technology-based teaching modules using Flip PDF software so that the implications are expected to arouse students' motivation to continue to like the subject. The research model used is development, with the results presented quantitatively and qualitatively descriptively. The subjects are divided into three, namely: a. material validators, media validators, and teachers. At the same time, the informants were taken from students and students of class VIII MTs Terpadu Berkah Palangka Raya. Data collection techniques use observation, tables or lists of questions, interviews, and documentation. The analysis techniques use three stages: data reduction, data presentation and data verification, and validity testing using triangulation techniques. The results showed that: 1). The development of vocabulary modules using flip pdf corporate software in class VIII at MTs Terpadu Berkah Palangka Raya is carried out with the ADDIE development model through 5 stages of development, namely: a) analysis, including performance analysis and need analysis; b) design, including display design on teaching materials made using storyboards; c) development, including the manufacture of learning materials; d) implementation, including product validation with material expert validators and media experts, then trials are carried out on students and English language subject teachers, namely small group and large group product trials and teacher responses; e) evaluation, including improvements according to suggestions and comments obtained by researchers at the implementation stage and the results of pretests and posttests. 2. Response results in the trial of students in class VIII MTs Terpadu Berkah Palangka Raya which was carried out in small group trials (5 people) obtained a percentage of 93.42% with a very good category, large group trials (1 class) obtained a percentage of 89.34% with a very good category. The response results were obtained by distributing student response questionnaires. And the results of the teacher response assessment can be known by using a questionnaire instrument in this case the English subject teacher. The assessment results obtained a percentage of 80.55% with a very good category. Keywords: Development, Vocabulary Module, Flip PDF Corporate Software